Importance of neuromuscular and metabolic determinants of 5 km running - Paavolainen, L.; Hakkinen, K.; Nummela, A.; Rusko, H. (Medicine & Science in Sports & Exercise, 1996)
Maximal anaerobic and aerobic running tests on the treadmill were used to determine maximal anaerobic power, maximal oxygen uptake, and ventilatory threshold in 12 endurance athletes. A 5 km time and 20 m maximal velocity test were conducted. Ventilatory threshold and maximal anaerobic power were the most important physiological determinants of 5 km time. It was also determined that the force and velocity characteristics of the neuromuscular system were just as important. Implication. The skill of running and the way forces are applied are just as important as physiological attributes for predicting 5 km running time. It is possible that measures of running economy along with maximal anaerobic power evaluations could lead to good predictions of 5 km performance.